Impacts of ethnoveterinary medicine integrated with livestock farm technologies on the performance and antimicrobial resistance of indigenous goats in South Africa –A review - Mthombeni, Lesedi; Osotsi, Joab Malanda; Novotni-Danko, Gabriella (Acta Agraria Debreceniensis, 2024)
Ethnoveterinary medicine and livestock farm technologies represent a junction of innovation and tradition with the aim to accomplish livestock systems that are resilient, productive, and sustainable to meet 21st century challenges, especially the antimicrobial resistance issue. This article aims to emphasise the impacts of integrating ethnoveterinary medicine with livestock farm technologies on the performance of indigenous goats in South Africa. With the growing concern over antimicrobial resistance in livestock, there is a pressing need for complementary approaches to the health of animals and their productivity. In this review, the aim evaluated whether an integrative approach could offer a sustainable alternative that benefits animal health and productivity while addressing the concerns of antimicrobial resistance. Comparative study designs across multiple indigenous goat farms were used to integrate specific medicinal plants in ethnoveterinary medicine with present-day livestock technologies that are used to monitor the effects on livestock performance indicators and antimicrobial resistance patterns. In the treated populations, the outcomes were indicative of substantial improvements in reproduction and growth rates, and alongside, there has been a notable decrease in the markers of antimicrobial resistance. Therefore, it is proposed that through these discoveries, the integration of these traditional and modern approaches not only improve the performance of indigenous goats but also contribute immensely to the mitigation of risks associated with antimicrobial resistance.